Pengaruh Utang Luar Negeri (Foreign Debt), Investasi Asing (Foreign Direct Invesment), Ketimpangan Ekonomi Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 2004-2023 - Angela Putri, Sherin; Winanto, Asis Riat; Abas, Sayid (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study investigates the impact of foreign debt (ULN), foreign direct investment (FDI), and economic inequality on Indonesia's economic growth, specifically GDP from 2004 until 2023. The findings show that foreign debt has a significant positive effect on GDP, with a strong correlation evidenced by a significance level of 0.000. In contrast, FDI does not significantly affect economic growth, as indicated by the t-test score of 0.449, exceeding the significance threshold of 0.05. Economic inequality also failed to show a significant effect on GDP, with a significance level of 0.084. The combined effect of foreign debt, FDI, and economic inequality explains 75.6% of the variance in GDP, as indicated by the R-squared value of 0.756. The study used statistical tests, including Durbin-Watson for autocorrelation, confirming the reliability of the results. Overall, this study underscores the important role of foreign debt in shaping Indonesia's economic landscape